Perancangan Sistem Informasi Akuntansi pada Toko Gomart Bengkalis - Nuryati, Rita; Fatimah, Siti; Nanda, Surya; Vebriany, Ulvi; Rahmayani, Mentari Tri Indah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The Gomart Bengkalis Store Accounting Information System is designed so that stores can calculate and record sales in accordance with good accounting principles and produce accurate, fast and precise information. Accounting information systems produce information such as inventory reports, cash inflow and outflow reports, and daily sales reports. This is especially important for shops that monitor company productivity and ensure that previously manual tasks are replaced with automated tasks. Practical, and database storage. More secure than previous systems. The information system design is implemented in the form of a web-based system and database that allows users to post journals, which are then processed by the computer system to produce the required information. The method used in this research to design this information system the SDLC method